Mobile-based Data Mining and Digital Technology Approaches to Improve Sustainable Tourist Experiences - Bahruni; Afkar, Muhammad Agha (Journal Mobile Technologies (JMS), 2023)
The tourism industry requires technological innovation to improve competitiveness and growth in the digital era. This study analyzes the use of data mining and digital technology as a tool to optimize tourist experience and increase customer satisfaction in the tourism sector. The development of applications based on data mining and digital technology is the main focus to explore tourist preferences and improve the efficiency of sustainable tourism management. Search features, bookings, and review systems are integrated into the application to facilitate tourist travel planning. The research methodology involves comprehensive data analysis to identify market trends and refine sustainable tourism management strategies. The results of the study provide benefits to the community, business entities, and government institutions in the tourism sector by improving the quality of tourist experience, customer satisfaction, and operational efficiency of sustainable tourism management. The urgency of the research lies in the potential for significant contributions to the development of the tourism sector and strengthening the national economy.